Spatial Control, Precarity, and Union Resistance in Digital Remote Work: An Analysis of ‘Work From Home’ in US and Canadian Call Centres - Doellgast, Virginia; O’Brady, Sean; Kim, Jeonghun (Work, Employment and Society, 2026)
This article analyses the experiences of US and Canadian call centre workers and their unions with the shift from physical call centres to ‘work from home’ (WFH) arrangements. Drawing on interviews, focus groups and a worker survey, the authors find that the shift enabled new forms of spatial control grounded in worker preferences for remote work and associated with different forms of precarity. Management control over the physical location of work could increase job insecurity; control over the costs and risk associated with WFH arrangements could increase income insecurity; and control over communication between workers and with their unions could increase collective representation and voice insecurity. Local unions engaged in modes of resistance to spatial control, but with uneven success. Findings suggest that labour power requires union strategies that both defend WFH rights and develop protections targeted at forms of precarity associated with being able to work from home.